Sanksi Pidana terhadap Pelaku Begal Bersepeda di Masa Pandemi Covid-19 - I Made Oka Wiradharma; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Warmadewa Press, 2022)
The act of violent theft carried out by forcibly seizing other people's property rights, acts of theft accompanied by coercion are regulated in the Criminal Code (Civil Law Book) article 365. The purpose of this study is to analyze the legal arrangements against cycling robbers during a social pandemic. covid-19 and to examine sanctions against cycling robbers during the covid-19 pandemic. The use of the case study methodology for this study is in the categorization of normative legal studies where the study is carried out through the collection of legal materials through the application of literature studies. This study uses the technique of collecting legal materials by recording, quoting, reading, and summarizing the literature that refers to sanctions, and the sentencing process. The results of this study indicate that criminal sanctions against cycling robbers during the covid-19 pandemic are based on Article 365 of the Criminal Code. Thus, this issue is in accordance with the provisions of the regulation of legal snares in the article in question regarding theft with violence.